Occurrence of Horseweed Biotypes with Low Susceptibility to Glyphosate in the States of Rio Grande do Sul, Paraná and Mato Grosso do Sul, Brazil - RIZZARDI,M.A. (2019)
ABSTRACT: Horseweed is an annual cycle weed naturally controlled by the herbicide glyphosate. However, the continued use of this product has selected tolerant and resistant populations. The objective of this study is to analyze the occurrence of horseweed biotypes with a low glyphosate susceptibility in the states of Rio Grande do Sul, Paraná and Mato Grosso do Sul. Seeds of horseweed plants (Conyzaspp.) that survived glyphosate applications were collected in RR soybean crops, totaling 137 samples from 37 municipalities. The seeds of the biotypes were sown, and the plants originated from them, when they reached the stage of four to six leaves, were subjected to a treatment with 1,440ga.e.ha-1 of glyphosate. According to the results, 108biotypes were not controlled and 29 were controlled by the application of glyphosate. Thus, 78% of horseweed biotypes evaluated are not controlled by the dose 1,440ga.e.ha-1 of glyphosate, and 22% are susceptible to the same dose. Evaluating the distribution per state, Paraná, Rio Grande do Sul and Mato Grosso do Sul presented 83%, 77% and 77%, respectively, of biotypes not controlled by glyphosate at the dose used. Thus, most of the collected horseweed biotypes present a low sensitivity to glyphosate, thus confirming the high horseweed distribution with a low susceptibility to glyphosate in Mato Grosso do Sul, Paraná and Rio Grande do Sul.